EL ANÁLISIS ESTADÍSTICO Y LAS CIENCIAS SOCIALES - Crivisqui, Enrique; PRESTA, Programa (La Sociología en sus Escenarios, 2010)
Abstract. There is a latent agreement between these two epistemologies when they reach his form - limit: the recognition that at the same time as they are different exists the necessity of the complementing of the statistical method and the sociological one. The social scientists accept of relative good degree this complementing and differentiates understanding it like a subordination of the instrument approach and formal from the social processes to the social theory. Nevertheless, it is common to find in the sociologists, critics not only to the explanations obtained like the imperfections of the statistical instrument. However, the statistical ones do not criticize the conceptual constructions of the sociological speech. Resumen. Los cientistas sociales aceptan de relativo buen grado esta complementación y diferencia entendiéndola como una subordinación de la aproximación instrumental y formal de los procesos sociales a la teoría social. Sin embargo, es común encontrar en ellos (los sociólogos) críticas no solo a las explicaciones obtenidas como a las imperfecciones del instrumento estadístico, lo que éste no hace de las construcciones conceptuales del discurso sociológico.